VARIASI PRONOMINA PERSONA BAHASA BALI DALAM LAYANAN KESEHATAN MASYARAKAT - Ni Made Suryati; Ni Made Dhanawaty; I Made Budiarsa; I Wayan Simpen (Fakultas Sastra Universitas Negeri Malang, 2018)
Abstract: Balinese language is divided into two dialects, namely Bali Dataran(DBD), and Bali Aga (DBA) dialect. The DBD variation happens vertically, but not in DBA. Some vocabularies in DBD that are classified into low(Tak-Alus/TA) are classified as common variants in DBA. This research aims to explore the Balinese personal pronoun variations in DBD which DBA in Sembiran(DS), and Seraya Timur(DST). The results, by applying the dialectology theory and correlation method or metode padan, showed that the personal pronouns of DS and DST varied lexically and phonologically. Lexically, the personal pronoun of first person singular in DBD /(ti)tiyaŋ/(A), /(i)–caŋ/ and /yaŋ/(TA) was realized as /oke/ and /kaka/ in DS also /(b)–iba/, /uke/, and /wane/ in DST. The second person singular /ragane/(A), /cai/ /ɲai/, and /ibə/(TA) in DBD, were realized as /cai/, /ɲai/, and /ŋko/ in DS also /cai/ and /ɲai/ in DST; and the third person singular /idə/, /dane/(A) and /(i) –yə/(TA) in DBD, were realized as /ya/, in DS and DST. Meanwhile phonologically, the realization of phoneme /a/ at the end of the word in DBD was realized as /ə/, in DS and DST was /a/. permalink/DOI: dx.doi.org/10.17977/um015v46i12018p073